Vasoactive peptides and the blood-brain barrier - Deli, Maria; Kis, Bela (Henry Stewart Talks, 2008)
Blood-brain-barrier (BBB) functions, permeability pathways and transporters modulated by vasoactive peptides, The BBB as a source and target of vasocative peptides, Angiotensins, Bradykinin, Adrenomedullin, Calcitonin-gene related peptide, Endothelins, Natriuretic peptides, Pituitary adenylate cyclase activating peptide, Substance P, Urotensin, Vasopressin, Potential use of vasocative peptides as modulators of BBB functions
Archived at 2017/09/14